2015
DOI: 10.17159/sajs.2015/20140133
|View full text |Cite
|
Sign up to set email alerts
|

Real-time measurement of outdoor worker’s exposure to solar ultraviolet radiation in Pretoria, South Africa

Abstract: The city of Pretoria in South Africa receives considerable solar ultraviolet radiation (UVR) because of its low latitude (22–35°S) and relatively clear skies. Certain meteorological factors affect the amount of solar UVR that reaches the ground; the most dominant factors being stratospheric ozone, cloud cover and solar zenith angle. It is known that overexposure to solar UVR may lead to the development of adverse health conditions, the most significant being skin cancer. Outdoor workers spend a significant amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
5
1
Order By: Relevance
“…Interestingly, exposure of car guards as a percentage of ambient solar UVR at 24% was higher than the 20% hypothesized in an earlier study albeit lower than the 84% and 46% reported before. Construction workers in Spain were found to receive a median of 13.9% of the total daily ambient solar UVR , and outdoor workers in a New Zealand study received 20.5% of the total daily available ambient solar UVR .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Interestingly, exposure of car guards as a percentage of ambient solar UVR at 24% was higher than the 20% hypothesized in an earlier study albeit lower than the 84% and 46% reported before. Construction workers in Spain were found to receive a median of 13.9% of the total daily ambient solar UVR , and outdoor workers in a New Zealand study received 20.5% of the total daily available ambient solar UVR .…”
Section: Discussioncontrasting
confidence: 73%
“…Studies quantifying personal exposure of outdoor workers in different industries have shown that workers are exposed to high levels of solar UVR, defined as levels above the International Commission on Illumination (CIE) Threshold Limit Value (TLV) of 1.09 SED . In a South African case study, an outdoor worker was exposed to 84% of the total daily ambient solar UVR . This implies that, depending on the ambient solar UVR levels, an outdoor worker of any skin type is likely at risk of sunburn on many days of the year.…”
Section: Introductionmentioning
confidence: 99%
“…There have only been two studies conducted in South Africa that evaluated occupational personal solar UVR exposure: one among outdoor parking area security staff (Nkogatse et al, 2019) and another of a school groundskeeper (Makgabutlane and Wright, 2015). This was the first known study to establish the personal solar UVR exposure of farmworkers in South Africa and goes beyond the earlier work by considering differences in body site and season.…”
Section: Discussionmentioning
confidence: 99%
“…Farmers in Italy received on average 15 SED per day or about 80% of the ambient solar UVR ( 12 ). Similarly, a South African school groundsman/gardener was exposed to 80% (4 SED) of the ambient solar UVR per day ( 13 ) while farmworkers were exposed to 46% (8–12 SED) of the ambient solar UVR per day ( 14 ).…”
Section: Population Groups and Outdoor Occupationsmentioning
confidence: 99%